Trefoil Factor Family (TFF) Peptides - Werner Hoffmann (Encyclopedia, 2021)
Trefoil factor family (TFF) peptides mainly consist of characteristic TFF domains, which contain about 40 amino acid residues, including 6 conserved cysteine residues. TFF peptides possess a single (mammalian TFF1 and TFF3), two (mammalian TFF2, Xenopus laevis xP2) or four TFF domains (X. laevis xP4). They exhibit lectin activities and are characteristic exocrine products of the mucous epithelia. Here, they play different roles for mucosal protection and the innate immune defense: TFF1 is a gastric tumor suppressor; TFF2 builds a lectin complex with the mucin MUC6, physically stabilizing the inner gastric mucus layer; and TFF3 forms a disulfide-linked heterodimer with IgG Fc binding protein (FCGBP), probably preventing the infiltration of microorganisms. Minor amounts of TFF peptides are endocrine products of the immune and nervous systems. Pathologically, TFF peptides are linked to inflammation. There are increasing indications that TFF peptides can antagonize cytokine receptors, such as receptors for IL-1β, IL-6, and TNFα (thereby acting as anti-inflammatory peptides). TFF peptides can probably also activate a variety of receptors, such as CXCR4. The TFF domain is a unique shuffled module which is also present in a number of mosaic proteins, such as zona pellucida proteins, sugar degrading enzymes and frog skin mucins. Here, their function seems to be defined by a lectin activity, which might even allow a role in fertilization.